2020
DOI: 10.1364/oe.389231
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and evolutionary algorithm studies of graphene metamaterials for optimized plasmon-induced transparency

Abstract: Machine learning and optimization algorithms have been widely applied in the design and optimization for photonics devices. We briefly review recent progress of this field of research and show data-driven applications, including spectrum prediction, inverse design and performance optimization, for novel graphene metamaterials (GMs). The structure of the GMs is well-designed to achieve the wideband plasmon induced transparency (PIT) effect, which can be theoretically demonstrated by using the transfer matrix me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 89 publications
0
35
0
Order By: Relevance
“…Somewhat surprisingly, economic theory provided one of the first intuition pumps for considering the nonhuman generators of machines: machines arise from the literal hands of human engineers but also the "invisible hand" of a free market; the latter set of pressures in effect "select, " without human design or forethought, which technologies proliferate (Beinhocker, 2020). More recently, evolutionary algorithms, a type of machine learning algorithm, have demonstrated that, among other things, jet engines (Yu et al, 2019), metamaterials (Zhang et al, 2020), consumer products (Zhou et al, 2020), robots (Brodbeck et al, 2018;Shah et al, 2020), and synthetic organisms (Kriegman et al, 2020) can be evolved rather than designed: an evolutionary algorithm generates a population of random artifacts, scores them against human-formulated desiderata, and replaces low-scoring individuals with randomly modified copies of the survivors. Indeed, the "middle man" has even been removed in some evolutionary algorithms by searching for novelty rather than selecting for a desired behavior (Lehman and Stanley, 2011).…”
Section: Machines Are Designed By Humans: Life Is Evolvedmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat surprisingly, economic theory provided one of the first intuition pumps for considering the nonhuman generators of machines: machines arise from the literal hands of human engineers but also the "invisible hand" of a free market; the latter set of pressures in effect "select, " without human design or forethought, which technologies proliferate (Beinhocker, 2020). More recently, evolutionary algorithms, a type of machine learning algorithm, have demonstrated that, among other things, jet engines (Yu et al, 2019), metamaterials (Zhang et al, 2020), consumer products (Zhou et al, 2020), robots (Brodbeck et al, 2018;Shah et al, 2020), and synthetic organisms (Kriegman et al, 2020) can be evolved rather than designed: an evolutionary algorithm generates a population of random artifacts, scores them against human-formulated desiderata, and replaces low-scoring individuals with randomly modified copies of the survivors. Indeed, the "middle man" has even been removed in some evolutionary algorithms by searching for novelty rather than selecting for a desired behavior (Lehman and Stanley, 2011).…”
Section: Machines Are Designed By Humans: Life Is Evolvedmentioning
confidence: 99%
“…All biological and artificial materials and machines strike careful but different balances between many competing performance requirements. By drawing on advances in chemistry, materials science, and synthetic biology, a wider range of material, chemical and biotic building blocks are emerging, such as metamaterials and active matter (Silva et al, 2014;Bernheim-Groswasser et al, 2018;McGivern, 2019;De Nicola et al, 2020;Pishvar and Harne, 2020;Zhang et al, 2020), novel chemical compounds (Gromski et al, 2020), and computerdesigned organisms (Kriegman et al, 2020). These new building blocks may in turn allow artificial or natural evolutionary pressures to design hybrid systems that set new performance records for speed, dexterity, metabolic efficiency, or intelligence, while easing unsatisfying metabolic, biomechanical and adaptive tradeoffs.…”
Section: The Interdisciplinary Benefits Of a New Science Of Machinesmentioning
confidence: 99%
“…[ 123–125 ] In photonic crystals, DNNs have been used to optimize the Q‐factor in nanocavities, [ 99 ] waveguide properties in fibers, [ 126 ] compute the band structure in 1D [ 127 ] and 2D [ 128–130 ] PCs, and predict edge states in topological insulators. [ 107 ] Last, several groups have utilized DNNs in the optimization of nanophotonic devices including plasmonic [ 131,132 ] and dielectric [ 102,133–137 ] waveguides, nanoantennas, [ 101,110 ] thermophotovoltaics, [ 138 ] power splitters, [ 133 ] biosensors, [ 139 ] smart windows, [ 140 ] and grating couplers. [ 141–143 ]…”
Section: Forward Modeling Of Aemsmentioning
confidence: 99%
“…In addition, the high tunability of graphene metalines can be combined with inverse design technology to design a more efficient photonics device [28]- [30]. In general, inverse design is converted to the optimization problem which can be solved by gradient based methods (such as adjoint variable method (AVM) [31]- [32]), gradient free methods (such as genetic algorithm (GA) [33]- [37]) and model based methods (such as machine learning [38]- [40]). As a representative algorithm of gradient based methods, AVM not only designs linear devices but also optimizes for the nonlinear devices in frequency domain, but it requires physical background to derive the gradient of objective function [31]- [32].…”
Section: Introductionmentioning
confidence: 99%
“…As a representative algorithm of gradient based methods, AVM not only designs linear devices but also optimizes for the nonlinear devices in frequency domain, but it requires physical background to derive the gradient of objective function [31]- [32]. Apart from the gradient-based methods, model based methods, such as artificial neural networks and random forest, are also used to inversely design the photonics devices [38]- [40]. However, in order to train the model whose inputs are physical parameters and outputs are electromagnetic responses, it requires a significant amount of time to generate the training instances and test instances [38].…”
Section: Introductionmentioning
confidence: 99%